On Statistically Estimated Optimistic Delivery inWide-Area Total Order Protocols - Mocito, José (2006)
Total order broadcast protocols have been successfully applied as the basis for the construction of many fault-tolerant distributed systems. Unfortunately, the implementation of such a primitive can be expensive both in terms of communication steps and of number of messages exchanged. To alleviate this problem, optimistic total order protocols have been proposed. This paper addresses the problem of offering optimistic total order in geographically wide-area systems. We present a protocol that outperforms previous work, by minimizing the average latency of the optimistic notification